HUBUNGAN PENGETAHUAN DAN MOTIVASI KELUARGA SUKU BADUY TERHADAP PERAWATAN POST PARTUM DI DESA KANEKES TAHUN 2024 - Rika Nopita; Bdn. Farida M Simanjuntak,Friska Junita (Jurnal Kesehatan, 2025)
According to the World Health Organization (WHO), the Maternal Mortality Rate (MMR) in Indonesia will increase by 59.69% in 2024. The increase in MMR occurred from 4,627 maternal deaths to 7,389. Most maternal deaths are caused by Covid-19, bleeding, hypertension, heart disease, postpartum infections, bleeding system disorders, abortion and others. to determine the relationship between post partum care according to Baduy customs and uterine involution in the Baduy village of Cisimeut Health Center in 2024. This type of research is quantitative with an exploratory design with a cross sectional approach. The sampling technique was total sampling, a total of 40 people. Primary data was obtained through interviews using a questionnaire, in the Baduy tribe area, Lebak Banten. With Guttman Analysis. it is known that the frequency distribution of mothers who received the most post partum care according to Baduy customs was 80% (32 people), the frequency distribution of mothers with the highest uterine involution process was good at 82.5% (33 people), there was a relationship between post partum care according to Baduy customs and uterine involution in Baduy villages with a p-value of 0.002 with an OR of 25. Conclusion: post partum care according to Baduy customs has a better impact on the uterine involution process compared to medical care.